Experience of 3D-Modeling in the Study of Muslim Medieval Gravestones in Kasimov - Vadim V. Ageev (Археология евразийских степей, 2024)
The article presents the first experience of studying the Muslim monuments in Kasimov with the help of three-dimensional computer graphics. The gravestones of the XVI–XVII centuries from the mausoleums of Shahghali Khan and Afghan-Muhammad Sultan were chosen for the study. Digital ocumentation of the sites was done according to the standards developed by RSSDA laboratory. At the field phase, photography was carried out using a camera. Models were created from the captured images with the possibility of applying different algorithms to improve their reading. As a result, it was possible to digitally preserve these monuments and virtually reconstruct some of them, verifying and correcting previous researchers. The poor physical condition of the sites was noted. It was possible to reconstruct partially the text of the epitaph, previously difficult for reading, with the help of mathematical surface visualization.